The shadow of a doubt? Evidence for perceptuo-motor linkage during auditory and audiovisual close-shadowing - Scarbel, Lucie; Beautemps, Denis; Schwartz, Jean-Luc; Sato, Marc (Frontiers in Psychology, 2014)
One classical argument in favor of a functional role of the motor system in speech perception comes from the close shadowing task in which a subject has to identify and to repeat as quickly as possible an auditory speech stimulus. The fact that close shadowing can occur very rapidly and much faster than manual identification of the speech target is taken to suggest that perceptually-induced speech representations are already shaped in a motor-compatible format. Another argument is provided by audiovisual interactions often interpreted as referring to a multisensory-motor framework. In this study, we attempted to combine these two paradigms by testing whether the visual modality could speed motor response in a close-shadowing task. To this aim, both oral and manual responses were evaluated during the perception of auditory and audio-visual speech stimuli, clear or embedded in white noise. Overall, oral responses were faster than manual ones, but it also appeared that they were less accurate in noise, which suggests that motor representations evoked by the speech input could be rough at a first processing stage. In the presence of acoustic noise, the audiovisual modality led to both faster and more accurate responses than the auditory modality. No interaction was however observed between modality and response. Altogether, these results are interpreted within a two-stage sensory-motor framework, in which the auditory and visual streams are integrated together and with internally generated motor representations before a final decision may be available.